Facial dimension on three-dimensional computed tomography in patients with epilepsy: A preliminary study (Bangladesh Journal of Medical Science, 2023)
Purpose: This study was undertaken to establish the facial anthropometric discrepancies in epilepsy and normal population of both genders.Methods: This Retrospective study was done in School of Dental Sciences, Universiti Sains Malaysia (USM). CT images weretaken from CT database archive from year 2010 to 2017 in Hospital Universiti Sains Malaysia (HUSM). The study group consisted of 9 epileptics & 9 healthy volunteers (aged between 42-56 years) who had no history of mixed racial parentage. 13 linear measurements were taken from 13 facial anthropometric landmarks including mandibles were first identified on each image according to standard definitions. The attained images were analysed using the Mimics Materialize measurement software ((Mimics 17.02 Materialise Leuven, Belgium).Results: The current study consisting 3 females vs 6 males representing in epileptic population & 2 female & 7 males in control populations. The results revealed sexual dimorphism in all the dimensional features of face, ocular region and the nasal region. The males having higher mean values than the females.In comparison with control male vs epileptic male showed significant variation onxygomaxillary (zm-zm) parameters. With regards of females there were no significant differences present within control groups and epilepsy groups. In thecontrol male group, result showed significantly (p= 0.04) longer mean values of nasion_alveoli (71.88 ±2.80 mm) compared to the control female group (65.63±0.94 mm) and highly significant difference were found in nasion_alveoli (na-al) and nasion_subnasale (n-sn) in between the epilepsy population of both sexes. The study was not concerned about age and ethnicity.Conclusion: The main objective of this work is to provide the standard values of epileptic patients’ data of both genders.The differences between that of epileptic patients against the control population may provide clear standards of variation with regards to facial analysis. This may contribute to a more in depth and nuanced phenotypic evaluation in the future. It has a large application to construct Forensic Medicine, Plastic Surgery, Orthodontics, Archaeology in the study epileptic populations. The facial, nasal and ocular, measurements among the most important cephalometric results that have been used to describe sexual differences.This study showed gender as an important factor in the description of human physiognomy.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 97-104